El mundo pasea por Uruguay: prácticas itinerantes del proyeccionista José Barrucci (s. XIX-XX) - Georgina Torello (Nuevo mundo - Mundos Nuevos, 2024)
The article reflects on itinerant practices and their implications in Uruguayan and continental culture spanning centuries. It focuses, for that, on the figure of the Italian itinerant entrepreneur, settled in Uruguay, José Barrucci. The earliest records of his activities date back to the late 19th century when he advertised his fixed views shows in the capital’s press. Subsequently, he began touring the interior of the country and neighboring nations, later incorporating the cinematograph. Through tracking his routes, his repertoires, the machines he used, and the propaganda strategies he developed, this text aims not only to reinstate the forgotten entrepreneur among the protagonists of entertainment in the country but also to reflect on the spectacular strategies employed by him, particularly on that media crossover so common in the field of attractions but insufficiently explored from an academic perspective, especially in the Latin American audiovisual context.